236 Novel Guidelines to Avoid Routine Blood Tests After Robotic Assisted Radical Prostatectomy (RARP). (4th May 2021) - Nathan, A; Hanna, N; Rashid, A; Patel, S; Phuah, Y; Flora, K; Sharma, A; Cleaveland, P; Kasivisvanatha, V; William, N; Mia, S; Collin, J; et al.
Abstract: Introduction: Patients undergoing RARP commonly require routine post-operative blood tests. This practice dates from an era of open surgery, with increased blood loss and complications. We aim to improve specificity of blood test requests with novel guidelines. Method: 1039 consecutive RARP patients at two tertiary urology centres in the UK were audited. Novel guidelines constructed based on risk stratified evidence from the initial audit were used to prospectively audit 133 patients. Results: 16% had clinical concerns post-operatively. 1% and 4% had an intra- and post-operative complication. Intra- or post-operative clinical judgement flagged post-operative complications in 99.9%. 80% had routine blood tests with no clinical concerns. 6% had delayed discharge due to delayed processing of blood tests. 0.9% received a peri-operative transfusion. Re-Audit Novel guidelines reduced the number of blood tests requested from 100% to 36%. Specificity in diagnosing a complication improved from 0% to 67%. Discharge delays reduced from 6% to 0% and no post-operative complications were missed (sensitivity 100%). Conclusions: Routine blood tests, without an indication, did not flag any additional post-operative complications. Blood transfusion is rare for RARP. Novel guidelines to request post-operative blood tests will reduce costs and discharge delays whilst maintaining appropriate patient safety and care.